Formulation of a Mapping Model for Opening New Study Programs based on Strategic Planning to Strengthen Higher Education Management in Indonesia’s Private Universities - Raskadi, Raskadi; Aedi, Nur; Prihatin, Eka; Soemarto, Soemarto (STKIP Yapis Dompu, 2022)
The main purpose of this study is to get an overview of the mapping of the opening of new study programs based on strategic planning for strengthening higher education management in private universities, this is motivated by the phenomenon of the proliferation of closed study programs, study programs that lack students, and the number of graduates who are not absorbed by IDUKA. The method used is a descriptive method with a qualitative approach, a case study of best practice strategic planning at Telkom University as a Vocational Private College in the West Java and Banten Regions, which on average 9 new study programs are opened per year. The process of collecting data through literature studies, documentation studies, interviews, and observations. The results show that the strategic planning that has been prepared describes the mapping of the opening of new study programs resulting from a systematic and comprehensive environmental analysis using the Penta Helix environmental analysis approach and the application of Competence Based Education (CBE) in Knowledge Management, thus mapping the opening of new study programs based on strengthening higher education management has been completed well described and projected that have interrelationships in socio-economic development that encourage a knowledge-based economy to innovate and entrepreneurship through beneficial collaboration and cooperation among universities, government, industry, civil society, and social entrepreneurs.